2019
DOI: 10.3906/tar-1807-74
|View full text |Cite
|
Sign up to set email alerts
|

Role of endogenous polyamines in the alternate bearing phenomenon in pistachio

Abstract: All pistachio cultivars used in production and in germplasm resources have the tendency of alternate bearing. In Turkey, Uzun, Kırmızı, and Siirt are the main cultivars used in pistachio production. Some of the cultivars have a strong tendency of alternate bearing, such as Uzun and Kırmızı, whereas some of them, such as Siirt, have a low yield after an 'On-year' season. Thus, alternate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…At the beginning, this problem was trying to be solved using several cultural applications, such as irrigation, pruning, and fertigation. Some researchers suggested that the competition between flower buds and food for fruit and assimilates is responsible for this phenomenon (Cetinkaya, 2004;Ulger et al, 2004;Baninasab et al, 2006;Mirsoleimani et al, 2014) while others stated that unbalanced nutrition was not the main cause of the inhibition of flower bud formation, and more attention should be paid to the hypothesis of PGRs (Baktır et al, 2004;Gomez-Jimenez et al, 2010;Vemmos, 2010;Gundesli et al, 2019). In higher plants, ABA and GA antagonistically regulate various physiological growth periods, including seed dormancy, seed germination, root growth, shoot elongation, leaf development, flowering, flower bud formation, abscission, and fruit development, as well as biotic and abiotic stresses (Vanstraelen and Benková, 2012;Liu and Hou, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the beginning, this problem was trying to be solved using several cultural applications, such as irrigation, pruning, and fertigation. Some researchers suggested that the competition between flower buds and food for fruit and assimilates is responsible for this phenomenon (Cetinkaya, 2004;Ulger et al, 2004;Baninasab et al, 2006;Mirsoleimani et al, 2014) while others stated that unbalanced nutrition was not the main cause of the inhibition of flower bud formation, and more attention should be paid to the hypothesis of PGRs (Baktır et al, 2004;Gomez-Jimenez et al, 2010;Vemmos, 2010;Gundesli et al, 2019). In higher plants, ABA and GA antagonistically regulate various physiological growth periods, including seed dormancy, seed germination, root growth, shoot elongation, leaf development, flowering, flower bud formation, abscission, and fruit development, as well as biotic and abiotic stresses (Vanstraelen and Benková, 2012;Liu and Hou, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We detected four dominant GAs in the different organs of pistachios, namely GA 8 , GA 19 , GA 29 and GA 44 (Tables 4 and 5). The literature contains studies that analyzed the hormone amounts of the fruit, leaves and flower buds of pistachio (Cetinkaya, 2004;Vemmos, 2010;Okay et al, 2011;Gundesli et al, 2019). Furthermore, Khalifah et al (1965) and Goldschmidt (1976) reported that citrus samples contained three GA-like substances, two of which were tentatively identified as GA 1 and GA 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, the Southeastern Anatolia region having both suitable geographical site and various climatic and soil conditions and pistachios are can be grown economically. In the production of pistachio, Southeast Anatolia Region covers 95% of the country's produc-tion area and 91.5% of the total production (Arpaci and Atli., 1996;Gundesli et al, 2018Gundesli et al, , 2019a. 'Uzun' pistachio is the most important and widely grown cultivar Gaziantep province of Southeastern Anatolia region (Ak and Fidan, 2013).…”
Section: Introductionmentioning
confidence: 99%